2013
DOI: 10.1107/s1600536813022204
|View full text |Cite
|
Sign up to set email alerts
|

3-Amino-1H-pyrazol-2-ium trifluoroacetate

Abstract: The asymmetric unit of the title salt, C3H6N3 +·C2F3O2 −, contains two independent 3-amino­pyrazolium cations and two independent tri­fluoro­acetate anions. The F atoms of both anions were refined as disordered over two sets of sites, with common occupancy ratios of 0.639 (12):0.361 (12). In the crystal, the cations and anions are linked via N—H⋯O hydrogen bonds, forming chains along [100] and [010].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Fluorinated pyrazoles have also been shown to possess interesting biological activities, for example, as herbicides (Ohno et al, 2004). Recently, crystal structures of 3,5-bis(4-fluorophenyl)-1-phenyl-4,5-dihydro-1H-pyrazole (Jasinski et al, 2010), 3-aminopyrazolium trifluoroacetate (Yamuna et al, 2013) have been reported by our research group. The crystal structures of some related compounds, viz., 1-trifluoroacetyl-3-trifluoromethyl-3a,8b-dihydro-1H,4H-indeno[1,2-c]pyrazole (Abdul-Ghani et al, 1995), ethyl 1-(4-chlorobenzyl)-3-(4-fluorophenyl)-1H-pyrazole-5-carboxylate (Ge et al, 2011) and ethyl 1benzyl-3-(4-fluorophenyl)-1H-pyrazole-5-carboxylate (Han et al, 2011) have been reported.…”
Section: S1 Commentmentioning
confidence: 89%
See 1 more Smart Citation
“…Fluorinated pyrazoles have also been shown to possess interesting biological activities, for example, as herbicides (Ohno et al, 2004). Recently, crystal structures of 3,5-bis(4-fluorophenyl)-1-phenyl-4,5-dihydro-1H-pyrazole (Jasinski et al, 2010), 3-aminopyrazolium trifluoroacetate (Yamuna et al, 2013) have been reported by our research group. The crystal structures of some related compounds, viz., 1-trifluoroacetyl-3-trifluoromethyl-3a,8b-dihydro-1H,4H-indeno[1,2-c]pyrazole (Abdul-Ghani et al, 1995), ethyl 1-(4-chlorobenzyl)-3-(4-fluorophenyl)-1H-pyrazole-5-carboxylate (Ge et al, 2011) and ethyl 1benzyl-3-(4-fluorophenyl)-1H-pyrazole-5-carboxylate (Han et al, 2011) have been reported.…”
Section: S1 Commentmentioning
confidence: 89%
“…For general background to pyrazole derivatives and their pharmacological activities, see: Ohno et al (2004); Patel et al (2010); Siu et al (2008); Sullivan et al (2006); Ragavan et al (2009Ragavan et al ( , 2010. For related structures, see: Abdul-Ghani et al (1995); Ge et al (2011); Han et al (2011); Jasinski et al (2010); Yamuna et al (2013). For standard bond lengths, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…For related structures, see: Baktır et al (2011);Fun et al (2012); Yamuna et al (2013). For bond-length data, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 98%
“…Because of these various interesting fields of application as well as their fairly assessable path of synthesis, the pyrazoline ring became a center of attraction for organic chemists. Crystal structures of some related compounds include 3, 5-bis(4-fluorophenyl)-1-(4-nitrophenyl)-4,5-dihydro-1H-pyrazole (Samshuddin et al, 2012), 5-(4-bromophenyl)-3-(4-fluorophenyl)-1-phenyl-4,5-dihydro-1H-pyrazole (Fun et al, 2012), 3,5-bis(4-fluorophenyl)-4,5-dihydro-1H-pyrazole-1-carbaldehyde (Baktır et al, 2011) and 3-amino-1H-pyrazol-2-ium trifluoroacetate (Yamuna et al, 2013). In view of the importance of the title compound, C 9 H 7 FN 2 , the paper reports its crystal structure.…”
Section: S1 Structural Commentarymentioning
confidence: 99%
“…For succinic acid derivatives used in chemicals, food and pharmaceuticals, see: Sauer et al (2008). For related structures, see: Kavitha et al (2013); Kettmann et al (2005); Koziol et al (2006); Parvez et al (2001); Yamuna et al (2013). Table 1 Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%